Analysis to Measure Resonance and Building Vulnerability Index in Southern Surabaya, East Java, Indonesia - Achmad Salvani Farrizi; Ariska Rudyanto; Agus Marsono; Relly Margiono; Dzikrullah Akbar; Ma’muri Ma’muri (Jurnal Penelitian Pendidikan IPA, 2025)
Microtremor analysis was conducted in southern Surabaya, East Java, to evaluate the seismic response of buildings using the Floor Spectral Ratio (FSR) and Random Decrement Method (RDM). Two buildings—a 9-story structure (Building A) and a 10-story structure (Building B)—were analyzed to assess their dynamic behavior and vulnerability to earthquake-induced shaking. As high-rise building development continues in Surabaya, such assessments are critical for enhancing structural safety. The FSR method provided estimates of natural frequency, amplification, and vulnerability index, while the RDM method determined the damping ratio and validated the natural frequency results. The findings show that the average natural frequency of Building A is 1.18 Hz (North-South) and 1.24 Hz (East-West), while Building B has 1.18 Hz and 1.17 Hz, respectively. Damping ratios ranged from 1 to 4% for Building A and 1 to 6% for Building B, both below the 10% critical threshold. The increasing vulnerability index with height indicates greater susceptibility to seismic amplification at upper floors. These findings confirm that both buildings meet the structural standards for multi-story building, reinforcing the importance of dynamic evaluation in earthquake-prone urban areas.